Ultrastructural basis of strong unitary inhibition in a binaural neuron - Gjoni, Enida (J Physiol, 2018)
KEY POINTS: Neurons of the lateral superior olive (LSO) in the brainstem receive powerful glycinergic inhibition that originates from the contralateral ear, and that plays an important role in sound localization. We investigated the ultrastructural basis for strong inhibition of LSO neurons using serial block face scanning electron microscopy. The soma and the proximal dendrite of an LSO neuron are surrounded by a high density of inhibitory axons, whereas excitatory axons are much sparser. A given inhibitory axon establishes contacts via several large axonal thickenings, called varicosities, which typically elaborate several active zones (range 1–11). The number of active zones across inhibitory axon segments is variable. These data thus provide an ultrastructural correlate for the strong and multiquantal, but overall variable, unitary IPSC amplitude observed for inhibitory inputs to LSO neuron. ABSTRACT: Binaural neurons in the lateral superior olive (LSO) integrate sound information arriving from each ear, and powerful glycinergic inhibition of these neurons plays an important role in this process. In the present study, we investigated the ultrastructural basis for strong inhibitory inputs onto LSO neurons using serial block face scanning electron microscopy. We reconstructed axon segments that make contact with the partially reconstructed soma and proximal dendrite of a mouse LSO neuron at postnatal day 18. Using functional measurements and the Sr(2+) method, we find a constant quantal size but a variable quantal content between ‘weak’ and ‘strong’ unitary IPSCs. A 3‐D reconstruction of a LSO neuron and its somatic synaptic afferents reveals how a large number of inhibitory axons intermingle in a complex fashion on the soma and proximal dendrite of an LSO neuron; a smaller number of excitatory axons was also observed. A given inhibitory axon typically contacts an LSO neuron via several large varicosities (average diameter 3.7 μm), which contain several active zones (range 1–11). The number of active zones across individual axon segments was highly variable. These data suggest that the variable unitary IPSC amplitude is caused by a variable number of active zones between inhibitory axons that innervate a given LSO neuron. The results of the present study show that relatively large multi‐active zone varicosities, which can be repeated many times in a given presynaptic axon, provide the ultrastructural basis for the strong multiquantal inhibition received by LSO neurons.